Перспективи розвитку туризму в Розвадівській територіальній громаді - Мельник, Уляна Володимирівна; Borshchevska, Uliana Volodymyrivna (Національний університет "Львівська політехніка", 2024)
Дипломна робота присвячена комплексному дослідженню туристично-рекреаційного потенціалу Розвадівської територіальної громади та визначенню перспектив розвитку туризму в регіоні. Актуальність теми зумовлена зростаючим значенням туризму як одного з ключових чинників соціально-економічного розвитку територій, зокрема в контексті децентралізації та активізації локальних громад [3; 5-6]. Актуальність питань оцінки туристично-рекреаційного потенціалу територіальних громад, а також стратегій розвитку туризму в умовах децентралізації та сучасних викликів зумовили велику кількість наукових праць та досліджень як серед науковців. Зокрема С. Пасєка і В. Джумурат [1] розглядають теоретичні засади дослідження туристичного потенціалу території Значну увагу щодо організації туризму в умовах воєнного періоду, акцентуючи увагу на ресурсах та їх оцінці саме нарегіональному рівні, приділили такі вчені, як А. А. Теребух та ін. [2]. У роботах Г. Я. Ільницької-Гикавчук [3], А. Мельник та ін. [4], О. Р. Роїк і А. А. Малоїд [5] здійснено комплексну оцінку туристично-рекреаційного потенціалу територіальних громад та на їх основі обґрунтовано рекомендації щодо формування стратегії розвитку туризму. Ряд авторів, зокрема О. І. Карий, Н. Ю. Глинський [6], О. С. Альбещенко і А. М. Вейц [7] досліджують об’єднання територіальних громад для ефективного використання туристично-рекреаційного потенціалу. Тоді як у роботі Н. Є. Паньків [8] запропоновано соціально-екологічний підхід до розроблення стратегії сталого розвитку туризму в громадах. Попри значну кількість досліджень зданої проблематики, залишаються нерозв’язаними питання інтеграції інновацій, залучення місцевих громад і врахування соціокультурних факторів. Ці аспекти потребують подальшого вивчення для забезпечення сталого розвитку туристичної сфери. Мета дослідження – комплексно дослідити туристично-рекреаційний потенціал Розвадівської територіальної громади, визначити ключові переваги та проблеми розвитку туризму, а також розробити стратегічні напрямки і рекомендації щодо ефективного використання ресурсів громади з метою сталого розвитку туристичної сфери. У роботі проведено теоретичний аналіз сутності, класифікації та особливостей розвитку різних видів туризму, зокрема зеленого, культурно-пізнавального, подієвого, сільського, екологічного, релігійного, промислового та техногенного, із врахуванням світового та українського досвіду функціонування туристичних систем у межах територіальних громад. Особлива увага приділена характеристиці специфіки туристичного розвитку саме в умовах місцевих громад, зокрема їх потенціалу, інфраструктури, соціально-економічного середовища та культурної спадщини. Практична частина роботи базується на комплексному аналізі туристично-рекреаційного потенціалу Розвадівської територіальної громади, включно з результатами анкетування, напівструктурованих інтерв’ю та SWOT-аналізу. Визначено ключові переваги та бар’єри розвитку туризму, проведено оцінку природних, культурно-історичних, інфраструктурних, соціально-економічних і техногенних ресурсів, які можуть бути ефективно використані для створення конкурентоспроможного туристичного продукту. Розроблено рекомендації щодо формування стратегії розвитку туризму, акцентуючи увагу на пріоритетних напрямках – зеленому, культурно-пізнавальному та подієвому туризмі, а також інтеграції інших видів туризму з метою диверсифікації туристичних пропозицій. Обґрунтовано необхідність активізації залучення інвестицій, розбудови партнерських відносин між місцевою владою, бізнесом та громадськістю, а також формування туристичних маршрутів і кластерів як засобів консолідації ресурсів та підвищення привабливості регіону. Результати дослідження можуть бути використані органами місцевого самоврядування, суб’єктами туристичної діяльності, науковцями та практиками для планування і реалізації ефективних заходів з розвитку туристичної сфери Розвадівської територіальної громади та подібних за характеристиками регіонів.

The bachelor’s thesis is devoted to a comprehensive study of the tourism and recreational potential of the Rozvadiv territorial community and the identification of prospects for tourism development in the region. The relevance of the topic stems from the growing importance of tourism as one of the key drivers of socio-economic development of territories, particularly in the context of decentralisation and the activation of local communities [3; 5–6]. The growing importance of assessing the tourism and recreational potential of territorial communities and of developing tourism strategies under the conditions of decentralisation and contemporary challenges has generated significant academic interest. For example, S. Paseka and V. Dzhumurad [1] explore the theoretical foundations for studying the tourism potential of territories. Considerable attention to tourism organisation during wartime – with an emphasis on local resource assessment – has been given by scholars such as A. A. Terebukh et al. [2]. In the works of H. Ya. Ilnytska-Hykavchuk [3], A. Melnyk et al. [4], O. R. Roik and A. A. Mалоїd [5], a comprehensive assessment of the tourism and recreational potential of territorial communities is provided, along with strategic recommendations for tourism development. Other researchers, such as O. I. Karyy, N. Yu. Hlynskyi [6], and O. S. Albeshenko and A. M. Veits [7], explore the consolidation of territorial communities for more effective use of tourism resources. In contrast, N. Ye. Pankiv [8] proposes a socio-ecological approach to sustainable tourism development strategies in communities. Despite the substantial body of research, unresolved issues remain regarding the integration of innovations, community engagement, and the consideration of sociocultural factors. These aspects require further investigation to ensure the sustainable development of the tourism sector. The aim of the research is to conduct a comprehensive assessment of the tourism and recreational potential of the Rozvadiv territorial community, to identify its key advantages and challenges for tourism development, and to formulate strategic directions and recommendations for the effective use of local resources in pursuit of sustainable tourism development. The thesis presents a theoretical analysis of the nature, classification, and specific features of various forms of tourism, including green, cultural, event, rural, ecological, religious, industrial, and technogenic tourism, with reference to global and Ukrainian experiences in the functioning of tourism systems within territorial communities. Particular attention is paid to the specificities of tourism development in local communities, including their potential, infrastructure, socio-economic environment, and cultural heritage. The practical section of the thesis is based on a comprehensive analysis of the tourism and recreational potential of the Rozvadiv territorial community, including data obtained from surveys, semi-structured interviews, and a SWOT analysis. Key strengths and barriers to tourism development are identified, alongside an assessment of the natural, cultural-historical, infrastructural, socio-economic, and technogenic resources that can be utilised to develop a competitive tourism product. Recommendations are proposed for the development of a tourism strategy with a focus on priority directions – namely green, cultural, and event tourism – while also emphasising the integration of other types of tourism to diversify the local tourism offering. The thesis substantiates the need to attract investment, develop partnerships between local authorities, businesses, and the public, and establish tourism routes and clusters as tools to consolidate resources and enhance the region’s appeal. The findings of this research can be utilised by local governments, tourism stakeholders, researchers, and practitioners in the planning and implementation of effective measures to promote the tourism sector in the Rozvadiv territorial community and other similar regions.
Prospects for Tourism Development in the Rozvadiv territorial community
Keywords: 6.242.00.00; туризм; туристично-рекреаційний потенціал; територіальна громада; стратегія туристичного розвитку; туристичні кластери; Розвадівська територіальна громада; tourism; tourism and recreational potential; territorial community; tourism development strategy; tourism clusters; Rozvadiv territorial community. REFERENCES 1. Pasieka; S.; & Dzhumur; V. (2023). Theoretical foundations of the study of the tourist potential of the territory. Visnyk Khmelnytskoho National University; (5); 42–59. https://doi.org/10.31891/2307-5740-2023-322-5-6 2. Terebukh; A. A.; Pankiv; N. Ye.; Roik; O. R.; Lushchyk; M. V.; & Moskvyak; Ya. Ye. (2022). The organization of tourism during the war period: resources and their evaluation: a monograph for students of specialty 242 “Tourism” of the Viacheslav Chornovil Institute of Sustainable Development of Lviv Polytechnic National University. Lviv–Drohobych: Posvit. 3. Ilnytska-Hykavchuk; H. (2022). Assessment of the tourist potential of the Skole territorial community of Lviv region. Herald of Khmelnytskyi National University. Economic Sciences; 304(2(1)); 113–115. https://doi.org/10.31891/2307-5740-2022-304-2(1)-14 4. Melnyk; A.; Melnyk; N.; Kacharovskyi; R.; & Yerko; I. (2021). Possibilities of using tourist and recreational potential in the conditions of decentralization (on the example of UTC of Volyn region). Human Geography Journal; 30; 67–75. https://doi.org/10.26565/2076-1333-2021-30-07Каразінська Наукова Періодика 5. Roik; O. R.; & Maloid; A. A. (2025). Assessment of the tourist and recreational potential of the Radekhiv territorial community. Tavriyskyi Scientific Herald. Series: Economics; (23); 273–281. https://doi.org/10.32782/2708-0366/2025.23.33 6. Karyy; O. I.; & Hlynskyi; N. Yu. (2020). Uniting the efforts of territorial communities to use their tourist and recreational potential. Halytskyi ekonomichnyi visnyk; (5(66)); 119–125. https://doi.org/10.32702/2307-2105-2020.5.15 7. Pankiv; N. Ye. (2020). Socio-ecological approach to the development of a strategy for sustainable tourism development of territorial communities. Scientific Bulletin of UNFU; 30(3); 71–76. https://doi.org/10.36930/40300312 8. Albeshchenko; O. S.; & Veits; A. M. (2024). Formation of a management system for the development of tourist and hotel entrepreneurship in territorial communities. Sustainable Economic Development; (3(50)); 52–57. https://doi.org/10.32782/2308-1988/2024-50-52